The art of conducting technique a new perspective - Farberman, Harold 1929-2018 (Alfred Music Publishing, 2009)
"Harold Farberman has conducted many of the world's leding orchestras [..] Mr. Farberman, a prolific composer [...], founded the Conductors Guild in 1976 [...]. He is the founder of the Conductors's Institute, a summer conducting program at the Hartt School where he continues to serve as Professor of Conducting."
Vortrag mit Dirigierbeispielen. Text 1997 als Buch erschienen bei Warner, Miami, Fl
Keywords: Geschichte 2009; Dirigieren; Film; DVD-Video